Chuva de sementes em remanescente de caatinga no município de Porto da Folha, Sergipe - Brasil - Gonçalves, Francineide Bezerra (2012)
Tropical dry forests are presented with great biological diversity and studies on the dispersion mechanisms and seed rain provide valuable information on dispersion standards, entrances and exits of seeds that act in the process of natural regeneration in preserved and/or degraded environments, as well as in the abundance, spatial distribution, density and species richness. Therefore, this study aims to identify strategies for the establishment of plant species according to the to the dispersal syndroms and characterize the seed rain in a remnant of Caatinga in the city of Porto da Folha, Semiarid of Sergipe, relating it to the dry and rainy season, in order to provide a better understanding of the interactions and dynamics of the place. For quali-quantitative evaluation of the present seed rain in the area, 25 collectors (confectioned in wood) were installed at 50cm above of the ground. The collectors were square shaped with a sample area of 1m2 with a depth of 10cm, and shading screen covering the bottom. The evaluations were performed monthly during 11 months. 4248 seeds belonging to 40 taxons were counted, from which 28 were identified to species level, four to genus and 12 classified as indeterminate. The identified species belong to 17 botanical families and are composed for four vegetation habits: trees, shrubs, herbs and lianas. The syndrome of predominant dispersion in the area, considering the number of identified species, was the ballistic dispersal (32,5%), followed of the anemochory (20%) and the zoochory (17,5%). As for the seeds density, the predominant dispersion syndrome found was anemocory (34,7%), exceeding the autocory (31,5%) and the zoochory (4,3%). The seed rain acts effectively in the self-regeneration of the vegetal community, due to the wealth and abundance of seeds deposited during the evaluation months, favoring the responsible mechanisms for the succession dynamics, in addition to contributing in the conservation and recovery of areas next to the observed forest fragment or other modified areas of Caatinga.